2006
DOI: 10.1002/app.24904
|View full text |Cite
|
Sign up to set email alerts
|

Novel organic modification of montmorillonite in hydrocarbon solvent using ionic liquid‐type surfactant for the preparation of polyolefin–clay nanocomposites

Abstract: ABSTRACT:The possibility of organic modification of montmorillonite (MMT) in hydrocarbon solvents by employing ionic liquid-type surfactants was investigated. As a first example, 1-methyl-3-tetradecylimidazolium chloride) was used to treat pristine MMT in xylene. The dispersion of MMT in xylene was significantly improved, the collected organifically modified MMT displayed a sufficiently enlarged interlayer spacing. The novel art of MMT organic modification is specifically advantageous to the preparation of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…[18][19][20] The desired amount of amino acid (1 and 2Â concentrations of the clay based on CEC) and 2 mL of hydrochloric acid in 50 mL deionized water was added into the mixture, The pH value of the solution was adjusted to 6-8 and stirring was continued for 4 h. A white liberated precipitate was filtered and washed with deionized water. The obtained wet precipitate was dried under vacuum at 80 C for 24 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] The desired amount of amino acid (1 and 2Â concentrations of the clay based on CEC) and 2 mL of hydrochloric acid in 50 mL deionized water was added into the mixture, The pH value of the solution was adjusted to 6-8 and stirring was continued for 4 h. A white liberated precipitate was filtered and washed with deionized water. The obtained wet precipitate was dried under vacuum at 80 C for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…In general, it is clear that all weight lose temperatures for the nanocomposites samples are higher than that of pure polymer, which can be attributed to the restriction of the motion of organic chains attached to MMT clay. 19 It is also obvious, that the increasing in the clay content plays an effective role in the increasing of thermal stability of these materials, which can be explained by the increasing in homogenous dispersion between the individual layers, which lead to increasing in the thermal stability. The TGA results of PGMA and PGMA-MMT are listed in Table II, which shows that the weight lose temperatures of nanocomposites are higher than that of pure PGMA.…”
Section: Structures and Properties Of Nanocompositesmentioning
confidence: 98%
“…On the other hand, the above‐mentioned properties of ILs also make them potent excellent additives for polymer. Recently, ILs have been widely used as ionic surfactants to improve the dispersion of montmorillonite, carbon nanotubes or other nanoparticles in polymer matrix. In addition, ILs also have been evaluated as plasticizers, lubricants, nucleating agents and antistatic agents in various kinds of polymers and shown promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Most imidazolium‐based ionic liquids containing long chain cations have been proved to posse higher thermal stabilities than alkyl ammonium,11–13 and were employed as clay (mostly montmorillonite) modifier in order to obtain enhanced thermal stability of the organoclay and nanocomposites. There are some reports on the alkyl‐imidazolium‐treated clay for the nanocomposite preparation from the thermoplastic matrixes, including nylon,14 polyolefin,15–17 polyester 12. Few studies have been reported on the thermosetting EP nanocomposite modified with the alkyl‐imidazolium‐treated clay.…”
Section: Introductionmentioning
confidence: 99%